How kinship systems change : on the dialectics of practice and classification - Parkin, Robert, 1950- (New York : Berghahn Books, 2021)
"Using some of his landmark publications on kinship, along with a new introduction, chapter and conclusion, Robert Parkin discusses here the changes in kinship terminologies and marriage practices, as well as the dialectics between them. The chapters also focus on a suggested trajectory, linking South Asia and Europe and the specific question of the status of Crow-Omaha systems. The collection culminates in the argument that, whereas marriage systems and practices seem infinitely varied when examined from a very close perspective, the terminologies that accompany them are much more restricted"--
List of illustrations -- Introduction -- Part I. Terminological change -- Kinship as classification : towards a paradigm of change -- Terminology and alliance in India : tribal systems and the North-South problem -- From Tetradic society to dispersed alliance -- Why do societies abandon cross-cousin marriage? -- Dravidian and Iroquois in South Asia -- Indo-European kinship terminologies in Europe : trajectories of change -- Part II. Crow-Omaha -- On the origin of Crow-Omaha terminologies -- Substitutability of kin and the Crow-Omaha problem -- The evolution of kinship terminologies : non-prescriptive forms of asymmetric alliance in Indonesia -- Conclusion -- Glossary -- Appendix -- Publications on kinship by Robert Parkin.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 14, 2021).
JSTOR
Keywords: Kinship; Marriage -- Social aspects; Cross-cousin marriage; Kinship -- India; Crow Indians -- Kinship; Omaha Indians -- Kinship; Parenté.; Mariage -- Aspect social; Mariage des cousins croisés.; Parenté -- Inde; Crow -- Parenté.; Omaha -- Parenté.; kinship; SOCIAL SCIENCE / Anthropology / Cultural; Cross-cousin marriage; Kinship; Marriage -- Social aspects; India